Native title and the politics of rejection: beyond the post‐political binary of consensus and dissensus in urban Aboriginal activism. (4th November 2018) - Cox, Shaphan; Jones, Tod
Abstract: This paper uses a settler colonial lens to highlight the limits of the post‐political while interrogating aspects of Indigenous politics and assertions of sovereignty in Perth, Western Australia. One of the ways in which Indigenous rights to urban space are being practiced in cities is through native title claims and negotiated settlements. In the south‐west of Western Australia, including in the capital city of Perth, native title negotiations have been characterised by protracted and acrimonious divisions between the Nyoongar custodians of the area and the State. Among members of the Indigenous population, highly publicised oppositional politics have also been constructed in the mainstream media between the South West Aboriginal Land and Sea Council and the Nyoongar Tent Embassy. In this paper, we analyse how they have been represented in media discourse and consider how both groups seek to articulate a politics of rejection of the settler colonial logic of elimination. We highlight the dangers that arise if and when researchers are seduced into adjudication on which group is properly political. Our aim is to demonstrate how the current native title regime disavows Indigenous sovereignty, which leads us to advance certain ways in which to understand the spatial effects of this politics of rejection and opposition to assertions of Indigenous sovereignty.